Công văn số 326/TANDTC-PC ngày 31 tháng 12 năm 2015 của Tòa án nhân dân tối cao về việc thi hành Khoản 2 Điều 1 Nghị quyết số 109/2015/QH13 của Quốc hội (2016)
Công văn số 326/TANDTC-PC ngày 31 tháng 12 năm 2015 của Tòa án nhân dân tối cao về việc thi hành Khoản 2 Điều 1 Nghị quyết số 109/2015/QH13 của Quốc hội.